Strategi Seleksi Tempat Bertelur Burung Mamoa (Eulipoa wallacei Gray, 1860) di Kecamatan Galela - Ahmad, Zulkifli (Biogenesis, 2014)
North Mollucas is the main of priority areas for global biodiversity. Not the entire beach in the Galela district be created nesting ground by birds of Mamoa. This is caused to existence of the key factors that the criteria for site selection, for example physical structure, safe location, and flanked by two barriers. The purpose of this study was to investigate the characteristics of nesting ground, vegetation composition and study the physical structure of the nesting grounds in the Galela district. Primary data were collected ; field characteristics of nesting ground, dimension and pattern layout eggs hatch hole, soil physical and chemical (temperature, moisture, aeration, pH, and organic matter content). To examine the relationship between temperature with depth, with a humidity range of the highest tides, used of simple regression analysis. Vegetation analysis conducted qualitative description by calculating the parameters of vegetation and Important Values. The method used for vegetation data are squares method designed in the form of a belt in a transect (bisect). The results showed that Mamoa birds make nests hatch for protection and convenience for cheepers. The temperature, moisture, aeration, the distance between the nest, the nest distance between the highest and the content of organic matter, is not a key factor in the site selection by the parents, but the determining factor in the process of egg incubation. The composition of the vegetation found on the beach Mamuya consists of 22 species, 13 species on Tiabo beach, and 17 species on the beach of Denamabobane. Stratification vegetation of tree level is dominated by Terminalia cattapa, and Hibiscus tiliaceus. At the level of the pole is Calothropis gigantera Dryand, Avicenia Sp., Caesalpinia bonduc, Terminalia cattapa, and Mangifera indica. At stake level is Terminalia cattapa, Scaevolia tacada, Rhizopora appiculata, Citrus aurantifolia and Mangifera indica. At the level of the shrubs is Bruguiera gymnorrhiza Lamk, Scaevolia taccada, Ficus septica, Anona muricata, and Morinda citrifolia, and undergrowth is Hypolitrium, Ipomea pescaprae, Phaseolus lunatus, Phaseolus foetida and Andropogon acciculatus Ritz.Keywords: Galela district, Mamoa birds, nesting ground, strategy, selection